When numbers remain silent: the protest potential of Kazakhstan’s youth amid social tension - Khamzina, Zhanna; Buribayev, Yermek; Buribayeva, Amina (Frontiers in Communication, 2025)
IntroductionWe analyze 2019–2024 dynamics of protes-related attitudes among Kazakhstani youth using secondary sources. The study asks: Why did standard surveys fail to register latent youth discontent prior to January 2022, and which survey‑adjacent indicators can improve early‑warning in settings with measurement and disclosure constraints?MethodsWe rely exclusively on published data and prior analyses. Latent protest potential is operationalized via three proxies: (1) acceptance of unsanctioned protest, (2) institutional trust, and (3) digital embeddedness. We synthesize national survey time series, youth subsamples, and open secondary indicators.ResultsWe identify a Kazakhstan‑specific “shock–trust–network” activation configuration (fuel‑price shock + trust downswing + decentralized coordination). Attitudinal openness to protest rose in 2022–2023 and moderated in 2024. Conversion from attitudes to on‑street participation appears constrained by perceived regulatory risks, social stigma, and economic vulnerability.DiscussionStandard survey instruments undercount sensitive attitudes due to question‑wording effects, social desirability, and frame coverage. Survey‑adjacent indicators that jointly track shocks, trust dynamics, and network capacity enhance early‑warning by monitoring preconditions rather than forecasting discrete events. With calibration, the framework is transferable to other contexts where conventional surveys have limited sensitivity on contentious topics.